Intestinal Short Chain Fatty Acids and their Link with Diet and Human Health - Ríos-Covián, David; Ruas-Madiedo, Patricia; Margolles, Abelardo; Gueimonde, Miguel; de los Reyes-Gavilán, Clara G.; Salazar, Nuria (Frontiers in Microbiology, 2016)
The colon is inhabited by a dense population of microorganisms, the so-called “gut microbiota”, able to ferment carbohydrates and proteins that escape absorption in the small intestine during digestion. This microbiota produces a wide range of metabolites, including short chain fatty acids (SCFA). These compounds are absorbed in the large bowel and are defined as 1-6 carbon volatile fatty acids which can present straight or branched-chain conformation. Their production is influenced by the pattern of food intake and diet-mediated changes in the gut microbiota. SCFA have distinct physiological effects: they contribute to shaping the gut environment, influence the physiology of the colon, they can be used as energy sources by host cells and the intestinal microbiota and they also participate in different host-signalling mechanisms. We summarize the current knowledge about the production of SCFA, including bacterial cross-feedings interactions, and the biological properties of these metabolites with impact on the human health